Polypectomy rate is a valid quality measure for colonoscopy: results from a national endoscopy database - Williams, Jason E. (2012)
BACKGROUND: The adenoma detection rate (ADR) is one of the main quality measures for colonoscopy, but it is burdensome to calculate and is not amenable to claims-based reporting. OBJECTIVE: To validate the correlation between polypectomy rates (PRs) and ADRs by using a large group of endoscopists. DESIGN: Retrospective study. SETTING: Community and academic endoscopy units in the United States. SUBJECTS: Sixty endoscopists and their patients. MAIN OUTCOME MEASUREMENTS: Proportion of patients with any adenoma and any polyp removed; correlation between ADRs and PRs. RESULTS: In total, 14,341 screening colonoscopies were included, and there was high correlation between endoscopists’ PRs and ADRs in men (Rs .91, P < .0001) and women (Rs .91, P < .0001). Endoscopists with PRs in the highest quartile had a significantly higher ADR than did those in the lowest quartile in men (44.6% vs 19.4%, P < .0001) and women (33.6% vs 11.6%, P < .0001). Endoscopists in the top polypectomy quartile also found more advanced adenomas than did endoscopists in the bottom quartile (men: 9.6% vs 4.6%, P = .0006; women: 6.3% vs 3.0%, P = .01). Benchmark PRs of 40% and 30% correlated with ADRs greater than 25% and 15% for men and women, respectively. LIMITATION: Retrospective analysis of a subset of a national endoscopic database. CONCLUSIONS: Endoscopists’ PRs correlate well with their ADRs. Given its clinical relevance, its simplicity, and the ease with which it can be incorporated into claims-based reporting programs, the PR may become an important quality measure.